Occurrence dataset of birds in the Xinjizhou National Wetland Park, Nanjing, China - Wei Shen; Zixi Zhao; Zheping Xu; Yong Zhang (Biodiversity Data Journal, 2023)
Xinjizhou National Wetland Park is located in Jiangning District, Nanjing, Jiangsu, China. With diverse wetland landscape types, Xinjizhou National Wetland Park maintains high biodiversity all year around. Meanwhile, as an important hub on the East Asian-Australasian Flyway, Xinjizhou National Wetland Park also occupies a core ecological position in the middle and lower reaches of the Yangtze River in Jiangsu Province. Therefore, carrying out systematic bird surveys and consequently understanding the distribution of birds and the seasonal variation of their communities can provide important insights for conservation. We conducted a one-year bird survey in the Xinjizhou National Wetland Park from 2021 to 2022 and provided occurrence datasets, including detailed species and geographic information.This dataset fills the knowledge gap in avian community composition for the Wetland Park and more importantly provides a basis to assess the conservation effectiveness of conservation measures taken in the Wetland Park.This occurrence dataset is the first public record of birds in Xinjizhou National Wetland Park. All data have been published on GBIF.